HAEMATOLOGY AND SERUM BIOCHEMISTRY OF PIG FED GROWER FEED FORTIFIED WITH COCOA (Theobroma cacao) SEED TESTA. - Akinduro, Victor Olabisi (Journal of Agricultural Sciences (Belgrade), 2022)
The on-farm attempt to cut down feed cost through bulk fortification of standard animal feed with available cheap conventional feed ingredients or wastes had been a normal practice without known empirical impact on livestock health and wellbeing. Therefore, this study determined the haematological parameters and serum biochemistry of pigs fed cocoa (Theobroma cacao) seed testa at varying inclusion levels in the formulated standard grower pig feed; 0% cocoa seed testa (T1), 25% cocoa seed testa (T2), 50% cocoa seed testa (T3), 75% cocoa seed testa (T4) and 100% cocoa seed testa (T5). Thirty (30), 8 weeks old pigs were randomly assigned to the five treatments of six pigs each and replicated thrice, with two pigs per replicate in a completely randomized design (CRD) experiment. The experiment lasted for 10 weeks. At the end of the feeding trial, blood samples were collected randomly from three pigs per treatment through the jugular vein using hypodermic needle and syringe for haematological analysis and serum biochemistry. This study recorded significant differences (P
Keywords: Blood parameters, Serum indices, pig health, pig diets, cocoa seed testa